Interactive family dynamics and Non-Suicidal Self-Injury in psychiatric adolescent patients: a single case study - Gatta, Michela; Miscioscia, Marina; Sisti, Marta; Comis, Ilaria; Battistella, Pier Antonio (Frontiers in Psychology, 2017)
Non-Suicidal Self-Injury (NSSI) is a common, multifaceted phenomenon among adolescents. Recent researchers have shown that a number of psychological and psychiatric correlates are implicated in the onset/repetition of NSSI, but those previous studies did not directly observe the family interaction patterns of this clinical population. In this paper, the quality of family interactions was observed using the Lausanne Trilogue Play procedure to deepen the specific interactive dimensions associated with Non-Suicidal Self-Injury in adolescents. The results of a single case study showed a lack of positive emotional exchanges, a parenting style expressing hostility, a high level of control and difficulties in triangulation. Through this method, the authors show that a better understanding of the role of family interactions is crucial and could improve the assessment and treatment of Non-Suicidal Self-Injurious behaviours. Research and clinical implications are discussed.